Strategy for Reducing Doubtful Receivables on Cash Performance of PT PLN (Persero) ULP Denai - Alamsyah Harahap; Renny Maisyarah (INFOKUM, 2025)
Doubtful receivables are one of the main challenges in financial management, particularly for public service providers such as PT PLN (Persero). This study aims to analyze strategies that can be implemented to reduce doubtful receivables and their impact on the company's cash performance. The research employs a quantitative approach by analyzing financial data from PT PLN (Persero) ULP Denai over a specific period. The results indicate that implementing more effective collection strategies, a digital customer monitoring system, and discount and incentive policies for timely payments significantly contribute to reducing doubtful receivables. Additionally, optimizing the prepaid electricity system (token-based payment) has proven to mitigate the risk of uncollectible receivables. By applying the right strategies, PT PLN (Persero) ULP Denai can improve operational cash flow, reduce financial burdens caused by uncollected receivables, and enhance efficiency in revenue management.